The ultrasonic cardiac output monitor (USCOM) as a tool in evaluating fluid responsiveness in pediatric patients underwent emergency surgery - Kurniyanta, Putu; Utariani, Arie; Hanindito, Elizeus; Ryalino, Christopher (Bali Journal of Anesthesiology, 2019)
ABSTRACTBackground: Assessment fluid adequacy in pediatric patients underwent surgery is a challenge for anesthesiologists. Hemodynamic parameters used as fluid monitoring sometimes don’t accurately provide valid information. Ultrasonic Cardiac Output Monitor (USCOM) is one of the non-invasive methods that are easy to operate and may provide various hemodynamic parameters monitoring information.Objective: Analyze the effectiveness of Stroke Volume Variation (SVV) and Stroke Volume Index (SVI) by using USCOM in assessing fluid responsiveness in preoperative pediatric patients who underwent emergency surgeries.        Method: This study was conducted on 16 pediatric patients underwent emergency surgeries. Before general anesthesia is given, blood pressure, mean arterial pressure, heart rate, cardiac index, SVV, SVI were recorded before and after administration of 10 mL/kg of fluid given within 20 minutes.Results: 10 subjects responded with SVV and SVI changes of more than 10% compared to 6 non-responders. SVV changes between responders and non-responders were 31.5±1.58 and 7.5±1.04, respectively. SVV percentage changes between responders and non-responders were 38.04±0.47 and 5.24±4.89, respectively.Conclusion: SVV and SVI recorded by USCOM showed significant fluid responsiveness changes in pediatric patients underwent emergency surgeries in 62.5% of the subjects.